Exploration of the possibility of acoustic emission technique in detection and diagnosis of bubble formation and collapse in valves - Alhashan, Taihiret; Addali, Abdulmajid; Amaral Teixeira, Joao (International Organization of Scientific Research, 2016)
The application of acoustic emission (AE) technique in detection and monitoring of bubble formation and collapse in valves are presented in this review. The generation of AE signals and the basic compositions of AE detection system are briefly explained. The applications of AE technique in valves are focused on condition monitoring and detection bubble formation (bubble cavitation), and leakage of water through valves. All results prove that the AE technique works well for detection and diagnosis of failures during valves.